Involvement of community pharmacy pharmacists in fecal immunochemical test screening without government support in Japan. - Yusuke Jin'o; Miharu Ushikai; Yuga Komaki; Koichi Masuda; Masahisa Horiuchi (PLoS ONE)
Colorectal cancer (CRC) is the third most common malignancy and second leading cause of death worldwide. However, the screening rate, which is a typical preventive measure, remains low. A community pharmacy pharmacist (CPP)-mediated procedure was used to increase the CRC screening rate. A total of 37 community pharmacies in Kagoshima, a core city in Japan, participated in this study. The results were statistically compared with the results of two procedures in Kagoshima City: hospital/clinic institution-mediated and health examination institution-mediated procedures. The cost was set at 1,100 JPY to perform a fecal immunochemical test, considering the costs as the self-payment of the other two procedures. In March 2023, 2,611 kits were distributed, and 273 tests were conducted under the research conditions. A significantly higher percentage of people in their 40s were tested using CPP-mediated procedures (35.2% vs. 14.3% in the hospital/clinic, and 21.8% in the health examination institution, respectively, p < 0.01). The percentage of participants who underwent a detailed examination at CPP facilities was significantly lower than in the other two groups (46.7% vs. 87.3% in the hospital/clinic, and 83.0% in the health examination institution, p < 0.05). In the CPP-mediated procedure, the test result turn-around time was approximately one day. Although a 2-day method was used, the implementation rate was 100%. The CPP-mediated procedure did not differ significantly from hospital/clinic or health examination institution procedures in terms of the number of detailed examination findings. In particular, the CPP-mediated procedure may address gaps by increasing the number of young people and people with reduced opportunities who receive CRC screening. The CPP-mediated procedure could be implemented as a new procedure with certain advantages. Moreover, it should be considered that this procedure can be implemented and sustained in society without government support.